Physico-chemical Characterization of Biochar from Selected Ligno-cellulosic Biomass for The Sustainable Utilization - ANJALI T B; Anand M; AKHILESH K B; MADHURAJ P K; RATHEESH KUMAR C S; ARCHANA WARAN (International Journal of Applied Biology, 2022)
Biochar is a thermal decomposition product known to mitigate climate change and a supplement to enhance soil fertility. The fine-grained, highly porous structure of biochar makes it a popular choice in environmental research. This study aims to assess the Physico-chemical properties and morphological changes in the biochar prepared from feedstocks: sawdust, sugarcane bagasse, and soapnut pith of Sapindus trifoliatus, native to the foothills of Western Ghats, Kerala, at a temperature of 300 oC and 600oC with 30 minutes residence time. The pyrolytic temperature and feedstock type may affect the yield, ash content, volatile matter (VM), fixed carbon (FC), and nutrient composition of biochar. The selection of these two factors is critical before proceeding with charring. The efficiency of biochar was determined through proximate, ultimate, and morphological characterizations. The pH of high-temperature biochar (sawdust biochar, sugarcane bagasse biochar, and soapnut pith biochar prepared at 600oC) was more alkaline (≥7) compared with low-temperature ones. The char yield was highest at 300oC, whereas the fixed carbon was limited. The VM/FC ratio of SDB600 at 1.09±2.3 represents the highest aromaticity and long-term stability. Therefore, SDB600 can be recommended for soil supplementation purposes. The macrospores were uniformly distributed throughout the biochar surface. Sugarcane bagasse pyrolyzed at 600oC (SBB600) possessed the minimum pore diameter (0.87-9.17µm), with the highest surface area; so that it could be an optimum habitat for soil microbiota as well as a suitable adsorbent for environmental remediation applications. The study suggests that biochar made from these ligno-cellulosic feedstocks is a sustainable tool and a value-added product for environmental management.